Longitudinal changes in body composition assessed using DXA and surface anthropometry show good agreement in elite Rugby Union athletes - Zemski, A. J.; Keating, S. E.; Broad, E. M.; Slater, G. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Rugby union athletes have divergent body composition based on the demands of their on-field playing position and ethnicity. With an established association between physique traits and positional requirements, body composition assessment is routinely undertaken. Surface anthropometry and dual-energy X-ray absorptiometry (DXA) are the most common assessment techniques used, often undertaken synchronously. This study aims to investigate the association between DXA and surface anthropometry when assessing longitudinal changes in fat-free mass (FFM) and fat mass (FM) in rugby union athletes. Thirty-nine elite male rugby union athletes (age: 25.7 ± 3.1 years, stature: 187.6 ± 7.7 cm, and mass: 104.1 ± 12.2 kg) underwent assessment via DXA and surface anthropometry multiple times over three consecutive international seasons. Changes in the lean mass index, an empirical measure to assess proportional variation in FFM, showed large agreement with changes in DXA FFM (r = .54, standard error of the estimate = 1.5%, p < .001); the strength of association was stronger among forwards (r = .63) compared with backs (r = .38). Changes in the sum of seven skinfolds showed very large agreement with changes in DXA FM (r = .73, standard error of the estimate = 5.8%, p < .001), with meaningful differences observed regardless of ethnicity (Whites: r = .75 and Polynesians: r = .62). The lean mass index and sum of seven skinfolds were able to predict the direction of change in FFM and FM 86% and 91% of the time, respectively, when DXA change was >1 kg. Surface anthropometry measures provide a robust indication of the direction of change in FFM and FM, although caution may need to be applied when interpreting magnitude of change, particularly with FM.